Análise termodinâmica e termoquímica via Cfd do processo de gaseificação de diferentes amostras de biomassa fecal - Venturott, Rodolfo de Melo (2017)
Nowadays there is a sanitation problem that affects billions of people around the world, especially in least developed countries. The lack of treatment of feces generates a proliferation of diseases, as diarrhea and cholera, causing malnutrition mainly in children that can lead even to death. The proper treatment of this waste is therefore essential to improve the quality of life of these affected people. Among the exiting solutions, one that is not very explored is gasification. Studies indicate the potential in the usage of fecal biomass to the production of combustible gases, since it has a high heating value if properly prepared, showing higher values than conventional biomass, like wood. In this context, the research presents a numerical approach in CFD for the simulation of a downdraft gasifier using fecal biomass. The methodology considers that the biomass particles that enter in the gasifier are analyzed in a Lagrangian reference using the Discrete Phase Model, and the gas that occupies the domain is analyzed in an Eulerian reference. The two phases interact with each other alternatively during the solution calculation until convergence is reached. The results seek to consider the influence of various parameters in the gasification process. The different sample compositions that were used indicated an impact of a higher amount of fixed carbon in the increase of the reactor temperature, which also impacts in the quality of the produced gases. The increase in moisture content reduced the gases heating value, like in the increase of tar, and also reduced the reactor average temperature. The relative humidity has an impact on the hydrogen gas production due to the addition of water vapor in the gasifier. The study however presented relatively high efficiencies, which can be attributed to the pyrolysis specification, and there were also stability problems that were solved with solution relaxation.